Effectiveness of Green Bond Issuance by Bank Mandiri in Emphasizing the Consistency and Implementation of Sustainable Finance - Hamsyah, Hamsyah; Goeliling, Ardhi; Sahabuddin, Romansyah (PINISI Discretion Review, 2024)
This research investigates the effectiveness of green bond issuance by Bank Mandiri in strengthening the consistency and implementation of sustainable finance. The research results show that the issuance of green bonds has a significant positive impact on the application of sustainable finance principles by Bank Mandiri. The presented data indicates that the amount of funds raised and the level of investor participation are very high, reflecting interest and commitment to sustainable projects. Green bonds also demonstrate superiority over other sustainable financial instruments, such as carbon taxes and green sukuk, with broader allocation flexibility and efficiency in fund raising. The issuance of green bonds also has a positive impact on Bank Mandiri's financial position, with changes in capital structure, cash flow, and investment strategies that support sustainability. In conclusion, the issuance of green bonds by Bank Mandiri successfully reinforces the commitment to sustainable finance, attracts investor interest, and supports projects that have a positive impact on the environment and society. Bank Mandiri has demonstrated that through green bonds, the bank can play an important role in creating a more sustainable and inclusive economy.